Les musées amérindiens : des lieux de mémoire ou d’anti-mémoire ? - Gérard Selbach (Revue LISA)
Native Americans have opened some 250 museums and cultural centers in the last twenty years for several reasons: to re-possess their patrimony, memorize their culture and maintain their identity. Their museums are spaces of cultural and educational experience, replacing split families who no longer transmit traditional values orally. They safeguard oral testimonies of the old people (recordings) and the sacred objects collected by the tribes after the vote of the NAGPRA in 1990. In the Navajo Museum in Window Rock, AZ, the tribe wants to regain control of its representation and narrate its version of its history. Museums are mnemonic tools. But, according to a Navajo medicine man, they do not need museums. The memory of the tribe is a living one and the culture is lived daily. The real place of memory is his brains (as the transmitter of the sacred words and mediator of the Spirits) and those of grandparents in every family. He is the possessor of the knowledge that makes up the Navajo philosophy: Hózhó, the Blessed Way, and healing ceremonies, which are links with the past, the ancestors and the Spirits. The true spiritual memory cannot be exhibited: it is lived and practiced in secret. Museums are evidence of a secularized world that tends to lose the memory of the past and of the sacred. They display the erosion of the transmission of knowledge and are henceforth places of anti-memory. However, for a young Navajo, the archives stored in the Navajo Museum will enable her to write the biography of her grandfather, Albert “Chic” Sandoval. If he helped two “anglo” linguists and anthropologists to become famous in the early 20th century, he also saved the Navajo culture, memory and language from disappearance. By doing so, he, in fact, applied the principle of Hózhó, i.e. of balance and harmony. Indian museums are ambivalent contact zones, built on compromises with the intrusive “anglo” society and experienced as the embodiment of the juxtaposition of two cultures: they in fact are both places of memory and anti-memory.